The toroidal curvatures of interplanetary coronal mass ejection flux ropes from multi-point observations - Lai, H. R.; Jia, Y.-D.; Jian, L. K.; Russell, C. T.; Blanco-Cano, X.; Luhmann, J. G.; Chen, C. Z.; Cui, J. (Frontiers in Astronomy and Space Sciences, 2024)
Interplanetary coronal mass ejections (ICMEs), characterized by their magnetic flux ropes, could potentially trigger geomagnetic disturbances. They have been attracting extensive investigations for decades. Despite numerous ICME models proposed in the past, few account for the curvature of the flux rope axis. In this study, we use conjunction observations from ACE, STEREO A and B, Juno and Solar Orbiter to analyze the evolution of the rope orientation of ICME flux ropes. Our findings indicate that the orientation of these ropes changes independently of the scale of the ropes or the distance they travel between spacecrafts. Furthermore, we estimate and compare the major radii of these flux ropes, uncovering a diverse range of distributions that do not seem to depend on the flux rope’s width. These results provide fresh insights and constraints for global ICME models, thereby contributing to the advancement of space weather research.